Evaluation of the effect of periodontal health and orthodontic treatment on gingival recession: a cross-sectional study - İsmail Gül; Resul Çolak; Orhan Cicek (BMC Oral Health)
Abstract Background and aim Periodontal health is a critical factor in the development of gingival recession, which may be influenced by orthodontic treatment and various patient-related factors. The aim of this study was to evaluate the prevalence of gingival recession observed during the retention phase after orthodontic treatment and the contributing etiological factors. Materials and methods A total of 96 patients (65 females, 31 males; mean age 20.39 ± 2.21 years) were included in the study during routine follow-up examinations in the retention phase, at least six months after the completion of non-extraction fixed orthodontic treatment and their sociodemographic data, oral hygiene habits, and clinical periodontal measurements were evaluated. The relationships between dentoalveolar cephalometric measurements obtained from lateral cephalograms and gingival recession and gingival phenotype were evaluated. The normality of the data was assessed using the Kolmogorov-Smirnov test, and Mann-Whitney U and Chi-square tests were applied for continuous and categorical variables, respectively. Logistic regression analyses were performed to evaluate risk factors. Statistical significance was considered as p < 0.05. Results Gingival recession was found to be more prevalent in thin gingival phenotypes compared to thick phenotypes and was observed to be more pronounced when bleeding on probing was 30% and higher (p < 0.05). It was observed that gingival recession increased with age (p < 0.05). No statistically significant difference was found between gingival recession and other periodontal clinical measurements, sociodemographic data, and oral hygiene habits (p > 0.05). No statistically significant relationship was observed between lower incisor protrusion and gingival recession (p > 0.05). Conclusions It was concluded that (i) gingival phenotype, bleeding percentage on probing, and age had a considerable effect on gingival recession, whereas orthodontic tooth movement had no significant effect, and (ii) after orthodontic treatment, despite the achievement of a well-aligned teeth and dental arch, the frequency of periodontal check-ups should be increased to reduce the risk of gingival recession. Clinical relavance Orthodontic treatment, consider periodontal conditions related to gingival recession, like thin phenotype and bleeding on probing.